2016
DOI: 10.1111/jar.12295
|View full text |Cite
|
Sign up to set email alerts
|

The Structured Assessment of Violence Risk in Adults with Intellectual Disability: A Systematic Review

Abstract: There is good quality evidence that risk assessment tools are valid for people with intellectual disability who offend but further research is required to validate tools for use with people with intellectual disability who offend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The current study provides a comprehensive evaluation of the predictive accuracy of the Static-99R in sex offenders with ID or borderline intellectual functioning. Because offending behaviour is often seen as challenging behaviour, and therefore, not always reported or criminally sanctioned in OIDs (Hounsome et al, 2018), certainly not in a forensic institution, unofficial incidents could be a better outcome measure than official recidivism. Therefore, we used several outcome measures in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study provides a comprehensive evaluation of the predictive accuracy of the Static-99R in sex offenders with ID or borderline intellectual functioning. Because offending behaviour is often seen as challenging behaviour, and therefore, not always reported or criminally sanctioned in OIDs (Hounsome et al, 2018), certainly not in a forensic institution, unofficial incidents could be a better outcome measure than official recidivism. Therefore, we used several outcome measures in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Since Pouls and Jeandarme (2015) and Hounsome et al (2018) reported predictive validity studies of four risk assessment instruments (Static-99/Static-99R/Static-2002/Static-2002R [Harris et al, 2003;Phenix et al, 2008;Phenix et al, 2016a;Phenix et al, 2016b], Rapid Risk Assessment for Sex Offense Recidivism [RRASOR; Hanson, 1997], Risk Matrix 2000 [Thornton et al, 2003] and SVR-20 [Boer et al, 1997]), only one recent article (related to Static-99R and Stable-2007) has been published (Delforterie et al, 2019). Results of studies in SOIDs were at best mixed and mostly involved the Static-99 and related versions (eight studies) and the RRASOR (four studies).…”
Section: Sexual Violence Risk Assessmentmentioning
confidence: 99%
“…Artificial intelligence (AI) has been used to support people with ID/DD in their education in terms of using games (de Castro et al , 2014), improving their risk assessment tools (Hounsome et al , 2018) and providing an engaging and enjoyable educational experience (Ricks and Colton, 2010). However, the results of this research analysis reveal these efforts have been on the same page but in different books.…”
Section: Discussion and Proposalmentioning
confidence: 99%
“…The extensive research on risk factors associated with criminality in people with and without IDD is the basis for the development of formal risk assessment tools. Hounsome et al (2018) reviewed the available instruments that assess risk for violence in people with ID. They identified 14 studies that assessed the validity of 18 risk assessment tools and found that all of them effectively predicted violent 317 behavior in adults with ID.…”
Section: Risk Assessmentmentioning
confidence: 99%